Kollektivvertrag̈e ub̈er Personalschlus̈sel in der Altenpflege; Collective agreements on staffing ratio in elderly care - Theresa Tschenker (Industrielle Beziehungen, 2019)
Die Arbeit in der ambulanten und stationar̈en Altenpflege muss von wenigen Fachkraf̈ten geschultert werden - zulasten der Beschaf̈tigten, Pflegebedur̈ftigen und Angehor̈igen. Beschaf̈tigte fordern deshalb mehr qualifiziertes Personal; eine Form, dies zu erreichen, sind tarifliche Regelungen ub̈er Personalschlus̈sel, sogenannte Entlastungsregeln. Im Folgenden werden zwei wesentliche Einwan̈de gegen solche Regelungen untersucht: das finanzielle und das rechtliche Argument. Die Analyse des Finanzierungssystems der Altenpflege und eine grundrechtsdogmatische Pruf̈ung zeigen, dass beide Einwan̈de nicht haltbar sind und Entlastungsregeln sowohl finanzierbar als auch rechtlich zulas̈sig sind. – – Work in elderly care in Germany is characterized by a lack of professionals. The workers, the elderly, and their relatives all suffer from the workload caused by the lack of employees. Therefore, workers are claiming more and better qualified staff. One way to reach this goal are collective bargaining agreements on staffing ratio. This article analyses two main objections against this claim: the financial and the legal argument. An examination of the financing system and an analysis of the fundamental rights of the employer and the employees show that both objections are insupportable. Staff ratios are both fundable and legally justified in collective bargaining.
Keywords: I11; J52; K31; 330; Altenpflege; Tarifverhandlungen; Personalschlus̈sel; Arbeitsbedingungen; elderly care; collective bargaining; staffing ratio; working conditions